Geopolitics of Hydrocarbons in the South-Eastern Mediterranean: Greek-Israeli-Cypriot Relations and the Importance of the EEZ of Kastellorizo. - Ioannis Mazis (Civitas Gentium, 2013)
Back in 2010, during my presentation at the Conference of the Institute of Energy of South East Europe (ΙΕΝΕ) on 8 February 2010, I had stressed the importance for Greece to proclaim an EEZ, and clarified the pertinent diplomatic arguments, together with its geopolitical and geostrategic advantages. Later, this communication was published in the Press («Estia», 8 January 2011) and on the Internet (skai.gr). Also, the weekly Epikaira published a complete study, co–authored by me and Dr. G.–A. Sgouros, in the form of a special insert entitled The Greek EEZ and Kastellorizo: Principles of a Geopolitical Analysis (issue 82, 12–18.5.2011). There are comparative demarcations, using Turkey’s baseline, in two ways: one using the Voronoi method and one using the median line principle, as applied also by competent international organizations). The arguments expressed in these documents are still valid, considering there has been no change, on the part of Greece, on the practicalities of the EEZ. There have been, of course, many promises and declarations from politicians, as there have been “extremely good intentions”. In the meantime, many views were also circulated, which were extremely dangerous, on “how far is Kastellorizo located”, as well as relevant, equally unfortunate views. We tend to forget, as my colleague Th. Karyotis also points out, that “there are 137 states having a 200 nm EEZ”.